Analysis of Students’ Learning Anxiety Factors in Offline and Online Learning of English - Hikmah, Nurul; Muhayyang, Maemuna; Abduh, Amirullah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aims to (1) identify the factors influencing students’ anxiety in offline learning, and (2) identify the factors influencing students’ anxiety in online learning. The subject of the research consists of 16 students, 8 of them are grade X and the rest are from grade XII in SMA Negeri 3 Barru. They were recruited using a purposive sampling technique. The results of this research indicate that (1) the factors influencing the students’ anxiety in offline learning are communication apprehension, fear of negative social evaluation, test anxiety, and students’ preparation; (2) the factors influencing the students’ anxiety in online learning are fear of negative social evaluation, test anxiety, learning method, assignments, long-term use of technology, network, and learning environment. Therefore, it can be concluded that the most influencing factors of students’ anxiety are test anxiety and fear of negative social evaluation.